Exploring the religious plants and their uses in Devghat Dham, Chitwan - Sharma, Hari Dev (BMC Journal of Scientific Research, 2020)
Nepal is one of the richest sources with respect to the occurrence of religious plants. Devghat Dham is one of the famous holiest place of central Nepal and also rich source of religious plants. The objective of this paper is to explore the socio cultural and religious value of plant species. Presented here are the descriptions of 50 religious plant species used traditionally by local people in the Devghat Dham for various religious activities. The species of plant were collected and identification by using participant observation and interview. Religious activities has played a significant role in conservation of plants.